Association Between Nipple Length and Early Breastfeeding Success in Postpartum Women: A Descriptive Correlational Study - Zeynem Yildirim Balkan; Serap Özdemir; Serap Balci (Breastfeeding Medicine, 2026)
Background: Breastfeeding is essential for improving newborn health and maternal-infant bonding. Objectives: To examine the association between nipple length and early breastfeeding success assessed using the LATCH score in postpartum women. Methods: This descriptive correlational study was conducted in the delivery room and obstetric clinic of a university hospital. The researchers aimed to include the entire eligible population without performing sample size calculations. A total of 335 mother-infant pairs were enrolled. The pre-lactation nipple lengths of primiparous mothers were measured, and early breastfeeding success was assessed twice using the LATCH Breastfeeding Assessment Tool. Data were collected using an information form, a follow-up form, and the LATCH assessment scale. Results: The mean nipple length of the mothers was 5.56 ± 3.51 mm, the mean nipple diameter was 17.60 ± 3.09 mm, the mean areola diameter was 6.50 ± 1.35 cm, and the mean time required for newborns to latch onto the breast was 194.77 ± 218.82 seconds. Regression analysis demonstrated that the models explained 60% and 63% of the variance in the LATCH-1 and LATCH-2 scores, respectively. Early breastfeeding success was significantly associated with several maternal nipple characteristics. Conclusion: Early breastfeeding success in primiparous mothers is associated with maternal nipple characteristics, particularly nipple morphology.